Metabolic mediators of the overweight’s effect on infertility in women with polycystic ovary syndrome - Kasra Jafari; Nooshan Tajik; Ashraf Moini; SeyedAhmad SeyedAlinaghi; Amene Abiri (Scientific Reports)
Abstract Women with polycystic ovary syndrome (PCOS) often experience infertility, potentially mediated by metabolic factors altered by elevated body mass index (BMI). While triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and fasting blood sugar (FBS) are known mediators in the BMI-infertility relationship, the extent of their mediation effects remains unquantified in prior studies. This study quantifies the mediation effect of these metabolic factors. We conducted a cross-sectional study on 669 women diagnosed with PCOS at a tertiary hospital in Tehran, Iran, from 2021 to 2023. Data on BMI, TG, LDL, HDL, and FBS were collected, with infertility defined as the inability to conceive after 12 months of unprotected intercourse. Mediation analysis was performed using the Karlson Holm Breen (KHB) method, adjusting for age. Higher BMI was associated with increased levels of TG, LDL, and FBS and decreased HDL, all of which (except for LDL) were linked to infertility. Mediation analysis revealed that after adjusting for age, TG, HDL, and FBS significantly mediated the BMI-infertility association, accounting for 52.98%, 79.19%, and 49.7% of the effect, respectively. Our study identified TG, HDL, and FBS as significant mediators of the BMI-infertility link, with over half of the association mediated through these factors. Targeting metabolic improvements may help reduce infertility risk in this population.